Open government data in Brazil: Spaces and intersections with Information Science - Rocha , Leonora de Oliveira; Nascimento Silva, Patrícia; Oliveira, Danielle Teixeira (Advanced Notes in Information Science, 2024)
In the context of information science, the topic of open data has emerged as a significant area of interest. This is due to the fact that the entire informational flow of data and information must be defined and managed. This involves elements related to its representation and organization, as well as its sharing and dissemination. The term “open data” is used to describe information from a variety of sources. When this information is related to government activities, it is defined as “open government data” (OGD). The objective of this study is to identify and characterize academic production on OGD in the Brazilian context, with a particular focus on mapping its location, knowledge area, and publication year. To this end, a bibliographic review was conducted based on the Brazilian Digital Library of Theses and Dissertations, which selected 68 documents for quantitative analysis in May 2023. The highest frequency of publication was identified in the South region, with 24 documents published and eight terms guaranteed to the Federal University of Santa Catarina in the areas of engineering and knowledge management and in the area of information science. It can be concluded that the majority of published works are concentrated in the areas of information science and computer science. Additionally, the regions that stand out in academic production are the South and Northeast. Regarding the frequency of publication over the years, the study indicated an irregular distribution with some periods of increased publication. The years with the highest concentration were 2019 and 2021. In future studies, other analyses, in addition to quantitative guidance, will complement the mapping of studies on OGD in Brazil.